Metformin degradation with combined UV/membrane - Jain, Gunjita (Nanyang Technological University, 2022)
According to the World Health Organization, the most common type of diabetes is type 2 diabetes. Diabetes happens when the human body becomes resistant to insulin or does not make enough insulin. Diabetes severely damages the vital parts of a body such as heart, eyes, and kidneys. There are about 422 million people around the world that are diagnosed with diabetes and this number is growing each year. The commonly used treatment drug for diabetes is Metformin, however a large percentage of Metformin, >90%, is excreted out by the human body within the first 24 hours of taking it. The Metformin is excreted in its unmetabolized form from the human body and hence this eventually makes its way to the water bodies. Numerous studies have reported the presence of Metformin in surface waters. Metformin treatment in wastewater treatment have reported using various processes. These processes include ultraviolet light (UV) irradiation, advanced oxidation process such as ozonation, use of H2O2 and CeO2 as a catalyst. In this study, we will investigate the degradation of Metformin using a combined UV – C irradiation and membrane treatment process where the metformin will be first treated with UV process followed by membrane filtration. A UV-Vis (visible) spectrophotometer will be used to measure the concentrations of Metformin in the solution for all the experiments. The effect of initial metformin concentration, UV intensity and pH on metformin degradation will be evaluated. The results show that increasing the initial concentration of Metformin leads to a decrease in the Metformin degradation rate due more Metformin molecules present in the solution that must be treated. Varying the pH did not seem to have a significant impact on the rate of degradation of Metformin. Varying the UV lamp intensity also did not seem to have much of an effect on the degradation of Metformin. However, it should be noted that for the experiment that used a neutral pH, pH = 7, it showed better degradation results as compared to using a lower or higher than pH = 7. The membrane treatment using NF 270 membrane for the solutions from the experiments that involved varying the initial Metformin concentration seemed to have removed the Metformin at a much faster rate. This meant that the initial solution does not have to undergo a very long treatment time for the UV irradiation and that it can just be put through the membrane cell to remove the Metformin. This study indicated that UV process may not be effective in degrading metformin, however it can significantly aid the removal of Metformin in membrane filtration using NF270.